PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP STOCK RETURN PADA PERUSAHAAN YANG BERKAITAN DENGAN LINGKUNGAN YANG LISTING DI BURSA EFEK INDONESIA - Eman Sukanto (STIE Pelita Nusantara Semarang, 2012)
This study aims to determine the effect of corporate social responsibility disclosure of the environmental, social and economic dimensions to stock returns. Measurement of CSR disclosure is based on Global Reporting Initiative (GRI) modified. For the stock return is computed using the market adjusted model represented with CAR (Cummulative Abnormal Return).This research conducted on the annual report of 51 listed companies in Indonesia Stock Exchange in 2010-2011 where samples are obtained by using purposive sampling techniques. The results showed that CSR disclosure of environmental, economic and social significantly positive influence on stock returns indicates that means investors are using this CSR information for investment decisions.